Aziz Al-Dein Abu Nasr Ahmed Ibn Abi Al Rajaa Hamid Ibn Mohammed Al Asbahani writer : The Writer who Fulfilled his Role in the Adminstration of the Seljuk State (472-526A.H /1079-1131 A.D) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This study aims to shed light at the personality of Almustawfi, the writer Aziz Al Dein Abu Nasr Ahmed Ibn Abi Al Rajaa Hamid Ibn Mohammed Al Asbahani, famously known as "Al-Aziz", at the period(472-526 A.H /1079-1131 A.D ). The study will cover the life of  Al-Aziz, and his family, the early beginning of his work in the management of the Saldjuk Empire, and his rise up the career ladder, and showing the importance of the position of Almustawfi, the owner of the royal treasury. Then, the study will aim at finding the reasons that led to his imprisonment, isolation, and murder, in addition to the extent of the role of the Seljuk administrative and military forces in overthrowing him.The study concluded that Al-Aziz was involved in an alliance with Al-Samayramy in overthrowing all those who opposed them in the administration of the state .. Therefore, when the other party who is to hostile to him  managed to control the administration of the state during the rein of Al-Darkezeini, this party overthrowed Al-Aziz in the context of the conflict between the different Saldjuk forces in the Administration and military.
Keywords: Al-Aziz Al-Asfahani; Fulfillment; Seljuk; Seljuk Administration